Tumor-infiltrating lymphocytes and tumor-associated macrophages in cancer immunoediting: a targetable therapeutic axis - Mukherjee, Sumon; Ghosh, Ahana; Chakraborty, Sourio; Basak, Udit; Mukherjee, Sumoyee; Das, Tanya; Sa, Gaurisankar (Frontiers in Immunology, 2025)
Immunotherapy has transformed the landscape of cancer treatment, offering hope to patients who were once considered beyond the reach of effective care. However, its success is restricted to a limited fraction of patients. This discrepancy in response is largely due to the complex and dynamic nature of the tumor immune-microenvironment. At the heart of this complexity is the concept of cancer immunoediting—a dynamic process through which the immune system both sculpts and is shaped by the tumor. This process unfolds in three key stages: Elimination, Equilibrium, and Escape, each representing a shifting balance between immune defenses and tumor adaptation. Central to this interaction are tumor-infiltrating lymphocytes (TILs) and tumor-associated macrophages (TAMs). TILs are frontline defenders in targeting tumor cells, while TAMs can either hinder or facilitate tumor growth based on their polarization. As cancer progresses, immune selection pressure induces phenotypic alterations that promote immune evasion, fostering an environment detrimental to effective immune response. This review explores the role of these immunological components in each phase of immunoediting and their impact on the efficacy or failure of immunotherapy. Gaining deeper insight into these interactions is crucial for developing advanced immunotherapies that reshape tumor microenvironment and expand the reach of immunotherapy to more patients.